Crustal Accretion in a Slow Spreading Back‐Arc Basin: Insights From the Mado Megamullion Oceanic Core Complex in the Shikoku Basin. (5th November 2020) - Basch, V.; Sanfilippo, A.; Sani, C.; Ohara, Y.; Snow, J.; Ishizuka, O.; Harigane, Y.; Michibayashi, K.; Sen, A.; Akizawa, N.; Okino, K.; Fujii, M.; et al.
Abstract: Oceanic core complexes (OCCs) represent tectonic windows into the oceanic lower crust and mantle; they are key structures in understanding the tectono‐magmatic processes shaping the oceanic lithosphere. We present a petrological and geochemical study of gabbros collected at the Mado Megamullion, a recently discovered OCC located in the extinct Shikoku back‐arc basin. Bathymetry of the Mado Megamullion reveals spreading‐parallel corrugations extending 25 km from the breakaway to the termination. Samples from several locations include peridotites, gabbros, dolerite, and rare pillow basalts. Gabbros range from granular to varitextured olivine gabbros and oxide gabbros. The emplacement of these gabbroic rocks within the oceanic lithosphere was followed by a multiphase tectono‐metamorphic evolution including (i) dynamic recrystallization within shear zones, developed under granulite‐ to upper‐amphibolite‐facies conditions, and (ii) intrusion of highly evolved melts forming felsic segregations. This tectono‐metamorphic evolution recalls that of the lower crust from other OCCs worldwide, demonstrating that this OCC exposes deep‐seated intrusions progressively exhumed by detachment faulting. Nonetheless, the Mado Megamullion lower crustal gabbros show an unusual crystal line of descent, different from what is reported from mid‐ocean ridge lower crustal rocks. We infer that the water‐bearing character of the primary melts in this back‐arc basin triggered the early precipitation of clinopyroxene, soon followed by amphibole and Fe‐Ti oxides. Such modifications in phase saturation are likely to be directly related to the back‐arc setting of the Mado Megamullion. If so, the phase assemblages of oceanic gabbros may be a diagnostic for the tectonic setting of lower crustal rocks in ophiolites. Key Points: The tectono‐magmatic evolution recorded at the Mado Megamullion recalls that of mid‐ocean ridge oceanic core complexes Lower oceanic crust in back‐arc basins shows a distinctive crystal line of descent triggered by the water‐rich character of the melt Phase assemblages in oceanic gabbros can be used as a diagnostic for the tectonic setting of formation of lower crustal rocks in ophiolites